Iran and the United States - Richard W Cottam (Univ. of Pittsburgh, 1988)
The book describes and evaluates the impact of U.S. policy on Iran. Given Iran's long history, the few decades of preeminent American influence, should appear momentary and of quickly passing importance. In fact, however, those few decades coincided with the most critical moment in a period of profound change in Iran. The case will be made that the impact of U.S. policy was to alter in major ways the direction of this change. In the other words, U.S. policy has changed in important respects the course of iranian history